ANALISIS FAKTOR MOTIVASI YANG MEMPENGARUHI PRESTASI BELAJAR SISWA PADA BIDANG STUDI MATEMATIKA DI SEKOLAH MENENGAH PERTAMA NEGERI 1 NAMLEA - Yusran Zakaria; M. Chairul Basrun Umanailo; Syafa Lisaholit; Dina Chamidah (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
This study aims to determine the effect of motivation on mathematics learning achievement of students at Namlea 1 Middle School. This research is a form of research